2000
DOI: 10.1002/(sici)1097-4636(2000)53:2<167::aid-jbm6>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Missing osteoconductive effect of a resorbable PEO/PBT copolymer in human bone defects: A clinically relevant pilot study with contrary results to previous animal studies

Abstract: PEO/PBT 70/30 (POLYACTIVE(R) 70/30), a degradable porous copolymer with elastic properties, was found to be osteoconductive in many animal studies. The aim of this study was to determine the osteoconductive effect in a human paired control iliac defect model. In seven patients undergoing anterior spinal interbody fusion surgery, two bicortical iliac defects for autograft harvesting were created. The defect size was identical for both defects measuring about 40 x 15 mm (group I). One defect was filled with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…128 In a human trail, PEGT-PBT (70% PEG) foam blocks were implanted into iliac crest defects and the bone healing was compared to untreated control defects. 129 Nine months after implantation, the PEGT-PBT foams resulted in limited inflammation but were encapsulated by fibrous tissue. The PEGT-PBT foams failed to calcify even after one year, and the un-treated control defects resulted in greater bone formation than the PEGT-PBT filled defects.…”
Section: In Vivo Applicationsmentioning
confidence: 99%
“…128 In a human trail, PEGT-PBT (70% PEG) foam blocks were implanted into iliac crest defects and the bone healing was compared to untreated control defects. 129 Nine months after implantation, the PEGT-PBT foams resulted in limited inflammation but were encapsulated by fibrous tissue. The PEGT-PBT foams failed to calcify even after one year, and the un-treated control defects resulted in greater bone formation than the PEGT-PBT filled defects.…”
Section: In Vivo Applicationsmentioning
confidence: 99%
“…Several subcutaneous and intra‐bone (tibia) implantations of dense blocks and porous films in rats showed bone bonding, calcification, and degradation for PEOT/PBT copolymers with high PEO content (60 and 70 weight percent PEO containing soft segment) 5–8. However, these effects were not seen after implantation of porous blocks in goat9 and human10 ilea. We intend to prepare porous PEOT/PBT scaffolds on which a patient's own bone marrow cells can be cultured.…”
Section: Introductionmentioning
confidence: 99%
“…In animal studies, Polyactive was shown to be surrounded by capillary-rich granulation suggesting that the polymer itself contributes to vascularization (43). Although Polyactive triggered the influx of immune cells at the implantation site in animal studies (43), application of the copolymer in the clinic was not associated with any side effects, and no inflammatory or abnormal cellular response was found 1 year after implantation (44). …”
Section: Challenges In Engineering An Artificial Transplantation Sitementioning
confidence: 99%